Caution, the use of humor may lead to confusion :Evaluation of a video podcast of the midwest teen sex show - Campo, Shelly; Askelson, Natoshia M.; Spies, Erica L.; Losch, Mary (American Journal of Sexuality Education, 2010)
Web sites about sexual health lack the interactivity, humor, and “viral” nature required to attract young adults. The Midwest Teen Sex Show (www.midwestteensexshow.com) is an interactive, humor-based Web site that provides sexual health information to young adults. One episode from the Web site was shown to six focus groups of young women, ages 18-30. Women found it funny, but some were offended or confused. Women were unable to differentiate between facts and humor; however, women could identify the key messages. Most women reported they would think about it later, visit the Web site, and share it with friends. Web-based interventions should use humor with caution.
Keywords: amériques; communication; contraception; discipline; humour; jeunes femmes*; médias; ressource en ligne; régions géographiques; santé; santé reproductive; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle; états-unis; étude qualitative